2022
DOI: 10.1186/s12890-021-01799-7
|View full text |Cite
|
Sign up to set email alerts
|

An 8-ferroptosis-related genes signature from Bronchoalveolar Lavage Fluid for prognosis in patients with idiopathic pulmonary fibrosis

Abstract: Background With the rapid advances of genetic and genomic technologies, the pathophysiological mechanisms of idiopathic pulmonary fibrosis (IPF) were gradually becoming clear, however, the prognosis of IPF was still poor. This study aimed to systematically explore the ferroptosis-related genes model associated with prognosis in IPF patients. Methods Datasets were collected from the Gene Expression Omnibus (GEO). The least absolute shrinkage and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Furthermore, the nomogram established in our study revealed the critical potential clinical significance of m7GPS by accurately predicting the short-term survival of IPF patients. Additionally, we confirmed that m7GPS and its constituent genes were reliable indicators for screening IPF patients from healthy individuals, while similar investigations were not discussed by the prognostic signatures of Prasse et al (2019) , Li et al (2021) , He et al (2022) . In conclusion, the m7GPS constructed in our study may serve as a novel biomarker for predicting the prognosis of IPF patients and screening IPF patients.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the nomogram established in our study revealed the critical potential clinical significance of m7GPS by accurately predicting the short-term survival of IPF patients. Additionally, we confirmed that m7GPS and its constituent genes were reliable indicators for screening IPF patients from healthy individuals, while similar investigations were not discussed by the prognostic signatures of Prasse et al (2019) , Li et al (2021) , He et al (2022) . In conclusion, the m7GPS constructed in our study may serve as a novel biomarker for predicting the prognosis of IPF patients and screening IPF patients.…”
Section: Discussionsupporting
confidence: 65%
“…m7GPS was an independent risk factor for the prognosis of IPF patients. The accuracy of m7GPS in predicting the 1-, 3-, and 5-year survival status of IPF patients was higher than that of the ferroptosis-related signatures constructed by Li et al (2021) , He et al (2022) . Moreover, compared to the signature identified by Prasse et al (2019) , the concordance indexes (0.76–0.80) of GAP stages combined with m7GPS were slighter higher than that (0.71–0.78) of GAP stages combined with the signature of Prasse et al (2019) , which suggested the advantage of m7GPS to some extent.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13,112 Bioinformatics analysis also supported that ferroptosis-related genes are significantly correlated with the development of IPF. [113][114][115] Moreover, some ferroptosis-related genes in the bronchoalveolar lavage showed prognostic value in patients with IPF. 113,115 Current studies mainly focus on the role of ferroptosis in the alveolar epithelial injury, fibroblast-to-myofibroblast transition, and epithelial-mesenchymal transition (EMT), all of which are important biological processes in the development of IPF.…”
Section: Ferroptosis and Pulmonary Fibrosismentioning
confidence: 99%
“…[113][114][115] Moreover, some ferroptosis-related genes in the bronchoalveolar lavage showed prognostic value in patients with IPF. 113,115 Current studies mainly focus on the role of ferroptosis in the alveolar epithelial injury, fibroblast-to-myofibroblast transition, and epithelial-mesenchymal transition (EMT), all of which are important biological processes in the development of IPF. It is now established that dysfunction of alveolar epithelial cells, especially alveolar type 2 (AT II) cells, drive the pathogenesis of IPF.…”
Section: Ferroptosis and Pulmonary Fibrosismentioning
confidence: 99%